Fintech Peer To Peer Lending Berbasis Syariah Sebagai Alternatif Permodalan UMKM Sidoarjo - Mega Novita Syafitri; Fitri Nur Latifah (ITB AAS INDONESIA Surakarta, 2023)
This study aims to see the role of sharia peer to peer lending fintech as an alternative solution to MSME capital problems in Sidoarjo. This research uses a qualitative methode of case studies by collecting secondary and primary data through interviews with business actors in Sidoarjo. Based on the results of interviews with MSME actors in Sidoarjo, literacy related to peer to peer lending fintech services is still low and the level of trust is also low. This is due to the lack of socialization from companies and the rampant fraud related to illegal fintech lending. However, there are also business actors who have trusted and used sharia peer to peer lending fintech services because the procedures implemented are easy and fast without collateral. Therefore, the role of sharia peer to peer lending fintech can be used as an alternative to MSME capital because it is easily accessible to micro-enterprises that are still far away in reaching banks.